Morbimortalidade por esquistossomose e aspectos políticos e operacionais de controle: análise integrada na região Nordeste do Brasil, 2000 a 2019 - Silva, Bárbara Morgana da (2021)
Introduction: Schistosomiasis mansoni persists as a health problem, especially in the Americas, in particularly in the Northeast of Brazil and the central region of Venezuela, where socioeconomic and environmental conditions favours the maintenance of transmission. Objective: To analyze the spatiotemporal patterns of morbidity and mortality and political operational aspects of schistosomiasis control in Northeast Brazil from 2000 to 2019. Methods: This is an ecological, time-series and spatial study, with descriptive and analytical approaches. We analyzed epidemiological and operational indicators from 1,794 municipalities by using secondary data from the Ministry of Health and in the political analysis, we considered official documents from states and electronic form filled out by managers of the Schistosomiasis Control Programs of these states. In the analysis of morbidity, we included cases of schistosomiasis from the Information System of the Schistosomiasis Control Program, the Notifiable Diseases Information System, and the Hospital Information System. In the study of mortality, we included death certificates from the Mortality Information System with schistosomiasis as an underlying or associated cause. Population data were obtained from the Brazilian Institute of Geography and Statistics. Results: Between 2000-2019, three states (Piauí, Pernambuco and Alagoas) mentioned the schistosomiasis policy in their Multiannual Plans according to the technical guidelines of the program. Among eight states that respond, six classified themselves as endemic. Between 2001-2017, 15,574,392 parasitological stool examinations were performed, 941,961 (6.0%) with positive results, mainly cities on the coast of Pernambuco, Alagoas and Sergipe. Between 2002-2017 there was a reduction from 7.4% to 3.9% in positivity and in the time trend of the detection rate ([APC-11.6*] [95% Confidence Interval -13.9 to -9.1]). There were 5,879 hospital admissions, 40.4% in Pernambuco. The hospitalization rate was reduced from 0.82 (2001) to 0.02 (2017) per 10,000 inhabitants. Between 2000 and 2019, there were 9,276 deaths from schistosomiasis, 51.0% in men, 40.0% ≥70 years, 54.8% in browns and 77.9% without residence in capital cities. Pernambuco presented highest proportion of deaths (53.9%) and Sergipe, the highest growth trend. There was a concentration of municipalities with standardized morbidity rate above average in Pernambuco, Alagoas, Sergipe, and Bahia, and with reduction, Piauí and Ceará. Spatial dependence was verified in spatio-temporal patterns of risk with clusters on the coast between Rio Grande do Norte and Bahia. Positive spatial autocorrelation and cluster formation was observed throughout the period. In conclusions: The Brazilian Northeast presented fragile public policies regarding the schistosomiasis surveillance system, remaining with high endemicity for the disease in the 19 years. The coastal region concentrates more cases, hospital admissions and deaths in residents of Pernambuco, Alagoas and Sergipe, with a heterogeneous spatial and temporal pattern. There was an improvement in epidemiological indicators in the period, however, in still high parameters. The evidence generated, provides elements that contribute to sustainability of control policies, particularly the strengthening of Primary Health Care. The control actions must go beyond the epidemiological dimension, comprising intersectoral policies aimed at the social and human development of these areas, eliminating the negligent character of this relevant endemic.